Centrifuge application of fibre Bragg gratings: pile axial loads and wall bending moments. Issue 4 (12th July 2022) - Song, Geyang; Xu, Jingmin; Heron, Charles M.; Marshall, Alec M.; Correia, Ricardo; Korposh, Sergiy
Abstract : One challenge for geotechnical centrifuge testing of soil–structure interaction problems is the reliable measurement of induced structural strains/forces. This paper presents a novel application of fibre Bragg grating (FBG) sensors for strain measurement within geotechnical centrifuge tests. FBG sensors have several advantages for centrifuge testing, in particular their small size and minimal self-weight. This paper gives an overview of recently developed installation and calibration procedures for FBG sensors within buried centrifuge model structures. The effect of thermal expansion/contraction of the materials (including both the fibre and structures) is considered and assessed. The precision and reliability of the FBG sensors are demonstrated using verification tests. The application of the FBG sensors is considered for two geotechnical problems, namely, pile jacking and a 'retaining wall' adjacent to a tunnel (acting as a protective wall to prevent an adjacent structure from tunnelling-induced ground movement). The results demonstrate that the FBG sensors can provide reliable measurements of pile axial strains/forces and protective wall bending moments. The paper provides evidence to support the routine adoption of FBG sensors for strain/force measurement of structures in geotechnical centrifuge modelling.